Guidelines for mine waste dump and stockpile design - Hawley, P. Mark; Cunning, John (CSIRO Publishing, 2017)
Developed and written by industry experts with extensive knowledge and experience, this book is an initiative of the Large Open Pit (LOP) Project. It comprises 16 chapters that follow the life cycle of a mine waste dump, dragline spoil or stockpile from site selection to closure and reclamation. It describes the investigation and design process, introduces a comprehensive stability rating and hazard classification system, provides guidance on acceptability criteria, and sets out the key elements of stability and runout analysis. Chapters on site and material characterisation, surface water and groundwater characterisation and management, risk assessment, operations and monitoring, management of ARD, emerging technologies and closure are included. A chapter is also dedicated to the analysis and design of dragline spoils. Guidelines for Mine Waste Dump and Stockpile Design summarises the current state of practice and provides insight and guidance to mine operators, geotechnical engineers, mining engineers, hydrogeologists, geologists and other individuals that are responsible at the mine site level for ensuring the stability and performance of these structures. --Publishers description.